Kantian Non-Evidentialism and its German Antecedents: Crusius, Meier and Basedow. Issue 3 (September 2019) - Chance, Brian A.
Abstract: This article aims to highlight the extent to which Kant's account of belief draws on the views of his contemporaries. Situating the non-evidentialist features of Crusius' account of belief within his broader account, I argue that they include antecedents to both Kant's distinction between pragmatic and moral belief and his conception of a postulate of pure practical reason. While moving us closer to Kant's arguments for the first postulate, however, both Crusius' and Meier's arguments for the immortality of the soul fail to anticipate the most important aspect of their Kantian counterparts. Developing the non-evidentialist features of Basedow's account of belief, I distinguish it from its Pascalian and Jamesian relatives and argue that it is the clearest antecedent to Kant's arguments for the first and second postulates. Finally, I consider the development of Kant's account of belief after the first Critique and discuss the broader implications of my analysis.